Punctuation in Translation: The Unseen Side of the Coin - Maasoum, Seyed Mohammad Hosseini; Mahdiyan, Mehdi (Mediterranean Journal of Social Sciences, 2012)
This paper critically surveys the role of three punctuation marks: the colon, the semicolon, and the comma, intranslating from English to Persian. It aims at investigating how problematic these punctuation marks can be and to what extentthe students’ familiarity with their pragmatic and metadiscourse functions can affect their translation from English to Persian. Toaccomplish this, twenty two graduate students of translation were selected and asked to translate some sentences from Englishto Persian. The results have indicated that only a minority of them were successful. The root causes of their poor performancecan be traced back to the lack of contrastive study on punctuation systems of English and Persian as well as lack of familiaritywith metadiscourse functions of punctuation marks.